2020
DOI: 10.1186/s13063-020-04416-w
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Acute Respiratory Distress Syndrome by Stromal Cell Administration in COVID-19 (REALIST-COVID-19): A structured summary of a study protocol for a randomised, controlled trial

Abstract: Objectives: The primary objective of the study is to assess the safety of a single intravenous infusion of Mesenchymal Stromal Cells (MSCs) in patients with Acute Respiratory Distress Syndrome (ARDS) due to COVID-19. Secondary objectives are to determine the effects of MSCs on important clinical outcomes, as described below. Trial design: REALIST COVID 19 is a randomised, placebo-controlled, triple blinded trial. Participants: The study will be conducted in Intensive Care Units in hospitals across the United K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…In the end, producing the MSC exos is no more complex then producing the MSC, but in comparison, when available, have the advantage of an ‘off the shelf’ reagent. Certainly, use of the highest quality MSC product exosomes to avoid possible increased risk of coagulopathy (Moll et al., 2020), in matched, randomized, controlled trials should be the rule (Gorman et al., 2020).…”
Section: Covid 19 Therapy With Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…In the end, producing the MSC exos is no more complex then producing the MSC, but in comparison, when available, have the advantage of an ‘off the shelf’ reagent. Certainly, use of the highest quality MSC product exosomes to avoid possible increased risk of coagulopathy (Moll et al., 2020), in matched, randomized, controlled trials should be the rule (Gorman et al., 2020).…”
Section: Covid 19 Therapy With Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…Furthermore, 14 patients (31.1%) required renal replacement therapy during ICU admission. 14 patients were enrolled in clinical trials(21,22). Other than low dose Hydrocortisone for septic shock, no patients received immune modulator or antiviral drugs outside the context of a clinical trial.…”
mentioning
confidence: 99%
“…Complicatedly, extensive studies reported the converse views that MSCs displayed the function of inhibiting cell activation of immune system [22]. Thirdly, according to a recent clinical trial [23], the evaluation of efficacy outcome lacked several indexes, such as oxygenation index and Sequential Organ Failure Assessment score. Overall, with incomplete data in our case, including cytokines, immune cells and efficacy indexes, it is difficult to precisely evaluate the exact effect of the UCB-MSCs treatment.…”
Section: Discussionmentioning
confidence: 99%